Parasternal approach for redo in ascending aorta pseudoaneurysm - Vaccarino,Guillermo Nuncio (2008)
Aortic ascending pseudoaneurysm is a rare complication following aortic root surgery. The surgical solution of the complication is rather demanding and complex, especially when reaching the mediastinum. The latter translates into an elevated morbidity and mortality. We present a case performed through a minimal anterior right thoracotomy, which allowed us to dissect between the pseudoaneurysm and the internal site of the sternum as a first step prior to a second esternotomy. By using this approach, we minimized bleeding risks and the possibility of aortic rupture. This technique could have the potential to be generally applicable in this complication after further evaluation.